(untitled) (Journal of Basic and Applied Research in Biomedicine, 2022)
A good knowledge of rice mineral nutrition could help to improve rice growing, in harmattan period, permitting thus, a continuous rice culture during all year round. However, rice nutrition in exchangeable cations of lowland soil is still unknown. It is why, three agronomic trials have been driven in a secondary lowland, in Cote d’Ivoire Guinean savannah zone to 2014 to 2017. Into a randomized completed blocks, ¦NPK ¦was applied according to the rates of 30 kg N ha-1, 60 kg P ha-1 and 50 kg K ha-1. Then, the rates of 50, 100 and 150 kg.ha-1 were added respectively in the treatments of Ca and Mg combined with 10, 20 and 30 kg Zn ha-1. Fertilizers were applied as basal and rice variety named ¦NERICA ¦¦L19 ¦was transplanted per hill of three plants spacing by 20 cm × 20 cm. At tillering and the booting stages ¦¦, 35 kg N ha-1 were applied respectively. NPK treatment ¦ was¦ considered as the control of the experimentation. The calcium was revealed as the most important cation inducing synergistic effect on rice nitrogen nutrition. The optimal dose was identified at 90 kg Ca ha-1 for highest grain yield (3.58 tha-1) in harmattan period. A fertilizer composes of 100 kgNha-1, 60 kgPha-1, 50 kgKha-1 and 90 kg Ca ha-1 was recommended for rice growing in Cote d’Ivoire Guinean savannah zone.